KEY MODELS FOR DIAGNOSING THE FINANCIAL RELATIONSHIPS OF ORGANIZATIONS - Utemuratova Bibikhon Danilovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
This article examines methods for diagnosing financial relationships of business entities, with a focus on the application of discriminant models for predicting financial stability. Special attention is given to the models of E. Altman and R. Taffler as tools for assessing the likelihood of financial distress and bankruptcy of organizations. The methodological foundations of these models, their analytical capabilities, and limitations in the context of the modern economy are considered. The study substantiates the feasibility of integrating Altman’s and Taffler’s models into a comprehensive system for diagnosing financial relationships, enabling the identification of crisis trends, assessment of financial stability, and improvement of managerial decision-making. The article concludes on the importance of adapting foreign methodologies to the specifics of the national economic environment.